Exploring business opportunities and different business models in Location Based Services - Juneja, Jasneet; Vijayan, Prijith (2010)
This report discusses Location Based Services, a booming sector in the mobile industry. Location Based Services (LBS) have been around for a decade but got revolutionized with the proliferation of GPS enabled mobile phones and improvements in communication and positioning technologies. The global mobile LBS revenue is expected to reach $ 12.7 billion by 2014 with Western European region predicted to hold a considerable share of the market. Despite the attractiveness of LBS market and interesting market forecast, most of the new LBS applications fail to generate reasonable due to poorly identified business opportunity, inadequate value proposition, inflexible business model and deficient marketing. Startups are looking for new innovative services bundling the existing service categories and viable business model which can generate considerable profit. This report presents a research work for identifying the business opportunities and viable business models in the mobile location based services industry. The report begins with explaining the research methodology and data collection techniques used to derive a conclusion. After defining the methodology, an overview of Location Based Services, the different components and classification of LBS applications is provided. A market research was performed through online surveys and industry reports to find the growth potential, trends and challenges in the LBS industry. The market analysis performed leads to the identification of business opportunities in three major LBS categories: Location Based Advertisement - Couponing, Pedestrian & Indoor Navigation and Location Based Social Networking. Attractive features and functionality from these categories are bundled then together to form an innovative service offering with the help of which the business model framework is explained. The research then uses academic framework to analyze different business cases that leads to the identification of different existing business models in consumer LBS market which are revenue based, distribution based and partner network based models. The report then presents a viable hybrid business model for the service identified using the four major components of business model: target market, distribution channel, partners network and revenue model based on the value proposition offered by the service.